2013
DOI: 10.1136/bmjopen-2013-002762
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting patients’ trust and confidence in GPs: evidence from the English national GP patient survey

Abstract: ObjectivesPatients’ trust in general practitioners (GPs) is fundamental to effective clinical encounters. Associations between patients’ trust and their perceptions of communication within the consultation have been identified, but the influence of patients’ demographic characteristics on these associations is unknown. We aimed to investigate the relative contribution of the patient's age, gender and ethnicity in any association between patients’ ratings of interpersonal aspects of the consultation and their c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
115
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 132 publications
(126 citation statements)
references
References 43 publications
10
115
0
1
Order By: Relevance
“…7 There are positive associations between patients' trust and their involvement in decisions about their health care, which increase with patient age. 32 Despite a greater frequency of GP consultations for older patients, 25 and recognition of the importance of patientcentred care for this age group, 16 there is variability in their participation in shared decision making 33 and inequality in primary healthcare outcomes. 17,26 This study involved detailed individual interviews with 20 older patients attending their GP.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…7 There are positive associations between patients' trust and their involvement in decisions about their health care, which increase with patient age. 32 Despite a greater frequency of GP consultations for older patients, 25 and recognition of the importance of patientcentred care for this age group, 16 there is variability in their participation in shared decision making 33 and inequality in primary healthcare outcomes. 17,26 This study involved detailed individual interviews with 20 older patients attending their GP.…”
Section: Discussionmentioning
confidence: 99%
“…A recent quantitative study 32 revealed that a sense of shared decision making was particularly associated with the expression of trust in doctors among older patients when compared with younger patients. This finding contrasts with previous literature suggesting that older patients may prefer a more passive focus on receiving information, rather than on active participation in decisions, 29,33 and with literature suggesting that trust can impede, as well as facilitate, older patients' involvement.…”
Section: Introductionmentioning
confidence: 99%
“…Studies suggest ethnic inequalities in doctor patient interactions (Burt et al 2016, Volz, Moore, and Belkora 2015, Ahmed et al 2015, Croker et al 2013, Wong et al 2014, Murray Garcia et al 2000, Lyratzopoulos et al 2012). In the UK people of South Asian descent generally report poorer doctor patient experiences compared with Caucasians (Ahmed et al 2015, Burt et al 2016).…”
Section: ! "mentioning
confidence: 99%
“…It comes as little surprise, therefore, that results from national patient satisfaction surveys tell us that an overwhelming majority of patients have trust and confidence in their GPs. 1 The uniqueness of the patient-doctor relationship in primary care lies in the fact that it crosses family generations and spans the entire spectrum of health and illness. However, in the past decade, government policy and the subsequent media coverage has meant that GPs are increasingly associated with money and this poses a real threat to this important bond.…”
mentioning
confidence: 99%